2018
DOI: 10.1111/cdev.13201
|View full text |Cite
|
Sign up to set email alerts
|

Visual Constancies Amidst Changes in Handled Objects for 5‐ to 24‐Month‐Old Infants

Abstract: Manual skills slowly develop throughout infancy and have been shown to create clear views of objects that provide better support for visually sustained attention, recognition, memory, and learning. These clear views may coincide with the development of manual skills, or that social scaffolding supports clear viewing experiences like those generated by toddlers during active object exploration. This study used a head‐mounted eye tracker to record 5‐ to 24‐month‐olds’ object views during repeated mother‐infant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Our finding that children with ASD had socially induced enriched visual experiences comparable to those of TD children are considered in light of recent reports of parents compensating for the immature skills of their TD young children when involved in a similar parent-child interaction context (Burling & Yoshida, 2019). In that study, parent involvement in showing objects to their child was higher during the early infant months (6 and 9 months), and objects that those parents brought close to the child were more likely isolated and larger in the child's view.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our finding that children with ASD had socially induced enriched visual experiences comparable to those of TD children are considered in light of recent reports of parents compensating for the immature skills of their TD young children when involved in a similar parent-child interaction context (Burling & Yoshida, 2019). In that study, parent involvement in showing objects to their child was higher during the early infant months (6 and 9 months), and objects that those parents brought close to the child were more likely isolated and larger in the child's view.…”
Section: Discussionmentioning
confidence: 54%
“…One study demonstrated that, while mothers were talking to their young infants (5 months to 24 months old), they actively used gestures in ways that influenced their babies' viewing experiences. Specifically, objects brought up close to the child were viewed by the child, thereby promoting SA (Yoshida & Burling, 2013;Burling & Yoshida, 2019). A number of studies on typical and atypical development also suggest the importance of parental responsivenessgaze, pointing, touching, object handling, object showing, tappingin children's SA Landry & Chapieski, 1989;Leekam, Hunnisett, & Moore, 1998;Carpenter, Pennington, & Rogers, 2002;Brigham et al, 2010;Yu & Smith, 2016).…”
Section: The Role Of Parent's Gesturing In Attentionmentioning
confidence: 99%
“…A third development, also related to joint attention, concerns infants' handling of objects. Burling and Yoshida (2019) examined infants between 5 and 24 months of age. They found that, early in development, parents draw infants' attention to objects through handling, but that parent handling of objects declines steadily over age.…”
Section: Developmental Differences After 18 To 20 Months Of Agementioning
confidence: 99%
“…The ability to successfully shift attention to the target of interest establishes the foundation of social learning and increases the learning efficiency that quickly maps the referent words to the seen objects ( Baldwin, 1993 ; Yu and Smith, 2012 ; Tenenbaum et al, 2014 ). Developmental researchers have studied infant object looking with respect to several aspects of parental social references, including parent’s gaze ( Brooks and Meltzoff, 2002 ; Caron et al, 2002 ), verbal phrases and labels ( Flom and Pick, 2003 ; Fulkerson and Haaf, 2003 ), hand actions ( Yu and Smith, 2013 , 2017 ; Deák et al, 2014 ; Burling and Yoshida, 2019 ), and the combined use of multimodal references by the parents ( Gogate et al, 2006 ; Tamis-LeMonda et al, 2013 ; Deák et al, 2018 ; Suarez-Rivera et al, 2019 ). The diverse social inputs serve as the perceptual foundation of word learning and as a basis for establishing the social coordination between infants and parents that is essential for sharing a common focus of attention.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that there are powerful input structures in everyday experiences with parents that create developmentally appropriate attention-directing links between heard words and seen referents/objects ( Gogate et al, 2006 ; Smith and Yu, 2008 ; Koterba and Iverson, 2009 ). Studies using head-mounted camera devices to record the infant centered views during object play found that infants often have a clear view of the object ( Yoshida and Smith, 2008 ; Yoshida and Fausey, 2019 ), and such clear viewing of an object is often accompanied by parental references (e.g., Yu and Smith, 2017 ; Burling and Yoshida, 2019 ; Yu et al, 2019 ). When the parent names the object at those socially synchronized moments, infants are more likely to learn the name of the object ( Gogate et al, 2006 ; Yu and Smith, 2012 ; Pereira et al, 2014 ; Yoshida and Fausey, 2019 ).…”
Section: Introductionmentioning
confidence: 99%